Analysis of Social Conditions of Heavy Slum Settlement Communities in Kapuk Village, Cengkareng District, West Jakarta - Lutfiyah Madinatunnisa; Alwin Alwin; Agung Adiputra; Ikhsan Hidayat (JAMBURA GEO EDUCATION JOURNAL, 2025)
West Jakarta is part of the special area of Jakarta which has developed for a long time as an old city and a metropolitan city. West Jakarta is a dense area that triggers the growth of slums. Slums are areas that do not have basic facilities such as electricity, drinking water, drainage systems, health facilities and public facilities, characterized by buildings that are physically and healthily unsuitable. Slums cause social problems such as poverty, and social problems are out of control. This research is a descriptive research with a Quantitative approach using data tabulation With the aim of this study, it discusses the Social Conditions in the Heavy Slum Settlement Community in Kapuk Village, Cengkareng District, West Jakarta. The result of this study is that there is a comparison of social conditions between slum RW areas in Kapuk Village The Kapuk region has a high immigrant population, which leads to inadequate educational facilities and limited access to clean water, sanitation, and education. Slums in this area can develop due to spatial planning, land status, and economic factors